The Influence of Leadership Style, Work Motivation, Work Discipline on Performance of PT LKM Demak Sejahtera Employees - Ainul - Maghfuroh; Rara Ririn Budi Utami; Luqman - Khakim (Politeknik Negeri Semarang, 2021)
Human resources have a very important role to achieve the goals and success of the company. One of them is supported by the behavior of employees who have competent performance. Leadership Style, Work Motivation, and Work Discipline are some of the factors that can affect the Employee Performance of PT LKM Demak Sejahtera. The purpose of this study was to determine the effect of leadership style, work motivation, and work discipline on the performance of PT LKM Demak Sejahtera employees. The data collection methods used were interview, literature review, and questionnaires which were distributed to 51 respondents using the census sampling technique. Data analysis methods include validity test, reliability test, t-test, F test, and coefficient of determination. The results showed that leadership style, work motivation, and work discipline had a positive and significant influence either partially or simultaneously on employee performance. Based on the coefficient of determination test produced a value on Adjusted R Square of 0.705, it means the contribution of the independent variables to the dependent variable is 70,5%. The remaining 0,295 or 29,5% is influenced by other variables not examined in this study.